Identifying potential engaging leaders within medical education: The role of positive influence on peers. (July 2015) - Michalec, Barret; Veloski, J. Jon; Hojat, Mohammadreza; Tykocinski, Mark L.
Abstract Background: Previous research has paid little to no attention towards exploring methods of identifying existing medical student leaders. Aim: Focusing on the role of influence and employing the tenets of the engaging leadership model, this study examines demographic and academic performance-related differences of positive influencers and if students who have been peer-identified as positive influencers also demonstrate high levels of genuine concern for others. Methods: Three separate fourth-year classes were asked to designate classmates that had significant positive influences on their professional and personal development. The top 10% of those students receiving positive influence nominations were compared with the other students on demographics, academic performance, and genuine concern for others. Results: Besides age, no demographic differences were found between positive influencers and other students. High positive influencers were not found to have higher standardized exam scores but did receive significantly higher clinical clerkship ratings. High positive influencers were found to possess a higher degree of genuine concern for others. Conclusion: The findings lend support to (a) utilizing the engaging model to explore leaders and leadership within medical education, (b) this particular method of identifying existing medical student leaders, and (c) return the focus of leadership research to the power of influence.